Reconceptualizing the Management–Auditor Relationship by Appling the General Partnership Contract to Challenge Independence: - Khalid Rasheed Al-Adeem (STIE Malangkucecwara, 2022)
The audit function in a corporate model can be a defective tool in monitoring executive management. Arguably, the Sarbanes-–Oxley Act (SOX) inadvertently has placed auditors in unwanted positions while increasing their independence. Auditors’ reliance on their clients for collecting information, financial dependence, and self-bias in processing information restrain them from neutrally and objectively judging corporate reporting. Mandated rules can never substitute integrity and the desired objectivity by shareholders. By reconceptualizing the result of the relationship as a general partnership where trust plays a critical role, this study considers the relationship between management and their auditors, offers an explanation about the audit firms’ behavior, and offers reasons for the failure of some audit for committing unethical actions. The analysis leads to testable empirical and policy implications. Accounting theorists should be on board critiquing and retheorizing positively but not normatively. A corporation with the absence of an objective party that shareholder count to attest corporate reporting impartially.